Malaysia : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2013)
The Bank Negara Malaysia (BNM) employs a well-developed risk-focused regulatory and supervisory regime. Despite this, a clear gap exists in the application of the supervision and regulation regime to financial holding companies. BNM is to be commended for its thoughtful and comprehensive self-assessment and efforts to help draft legislative changes and to make administrative changes to address the areas of improvement revealed by the self-assessment. Improvements should be made in the transparency of elements of BNM's supervisory expectations, its domestic coordination and information-sharing arrangements, and legal protection for staff.